Student retention and learning analytics : a snapshot of Australian practices and a framework for advancement : final report. - Colvin, Cassandra; Rogers, Tim; Wade, Alexandra; Dawson, Shane; Gasevic, Dragan; Shum, Simon Buckingham; Nelson, Karen; Alexander, Shirley; Lockyer, Lori; Kennedy, Gregor; Corrin, Linda; Fisher, Josie (Office for Learning and Teaching, 2016)
The analysis of data from user interactions with technologies is changing how organisations function, prioritise and compete in an international market. All industries have been influenced or impacted by the so-called digital revolution and the associated analysis of user data. In the higher education (HE) sector this wave of data analytics has flowed through to the concept of learning analytics (LA). This field of research has been touted as a game changer for education whereby the outcomes of LA implementations will address core education challenges. These include concerns regarding student retention and academic performance, demonstration of learning and teaching quality, and developing models of personalised and adaptive learning. While there is broad consensus across the sector as to the importance for LA there remain challenges in how such endeavours are effectively and efficiently rolled out across an organisation. The lack of institutional exemplars and resources that can guide implementation and build institutional capacity represents a significant barrier for systemic adoption. This report seeks to unpack these challenges to institutional adoption and provide new insights that can aid future implementations of LA and help advance the sophistication of such deployments. The study does so by interrogating the assumptions underpinning the adoption of LA in the Australian University sector and contrasting this with the perspectives of an international panel of LA experts. The findings and recommendations highlight the need for a greater understanding of the field of LA including the diversity of LA research and learning and teaching applications, alongside the promotion of capacity building initiatives and collaborations amongst universities, government bodies and industry. [Executive summary]